Stability of protraction Facemask/Rapid Maxillary Expansion in skeletal class III malocclusion with maxillary deficiency: Rapid Review - Citra Elitasari Rigel PUTRI; Avi LAVIANA; Gita GAYATRI (Journal of Syiah Kuala Dentistry Society, 2022)
this study aimed to evaluate the stability of PFM/RME outcomes in class III skeletal malocclusionwith maxillary deficiency performed during childhood. Electronic database search conducted from 2011-2020 withcriteria RCT, clinical trials, and cohort studies with a treatment group of class III skeletal malocclusion withmaxillary deficiency patients, using PFM/RME and a minimum of 2 years follow-up. The PFM/RME device hasbeen commonly used for maxillary protraction in cases of maxillary growth deficiency and is used duringchildhood. The stability of the PFM/RME protocol results aims to maintain the best possible treatment results.There were 439 articles from the preliminary search. Six articles were included in this study, two articles were RCTtypes, and the other four were CCT types. Clinical evaluation and cephalometric are used to evaluate skeletal anddentoalveolar changes. 68%-90% of participants maintained overjet until the follow-up period ended. PFM/RMEprotocol reduced the need for orthognathic surgery by 3,5 times compared with a control group with notreatment.PFM/RME treatment can effectively show in the short term from skeletal dan dentoalveolar changes.There were relapses during the long-term follow-up period. Further evaluation and research are needed regardingthe long-term stability of PFM/RME outcomes. KEYWORDS: Class III malocclusion, Growth modification, Maxillary deficiency Protraction facemask (PFM), Rapidmaxillary expansion (RME)